Spiritual Transitions at the End of Life - Cummings, Rachel (Anthropologica, 2025)
This article considers the liminality of dying through the lens of “deathbed experiences”: reports of events occurring towards the end of life subject to multiple, potentially conflicting explanations, both medical and transcendent. Examples include a dying person reporting conversation with a deceased relative or reaching towards something unseen. While deeply meaningful and metaphysically significant to some, others explain them in material terms: as opioid toxicity, delirium or similar. These differing explanations bring an ontological liminality into the clinical realm. Based on ethnographic research within a UK hospice and 42 interviews with palliative care staff, this piece puts deathbed experiences in conversation with anthropology’s “ontological turn.” It compares the responses of clinicians to those of ethnographers confronting ontological difference. Drawing specifically on the methodological strain within this literature, it argues for care in such moments to be informed by “recursivity.” The article considers the consequences of this recursive form of care more broadly with reference to the biopsychosocial model. It ends with a discussion of how to do research about recursive care in a suitably recursive way.